MENINGKATKAN PENGALAMAN BELAJAR: PERANGKAT PSIKOLOGI UNTUK MEMAKSIMALKAN PEMBELAJARAN EFEKTIF - Fauziah Nasution; Hikmah Lubis; Sakinah Azzahra (JIP: Jurnal Ilmu Pendidikan, 2023)
Effective learning is the main goal in education. Educators are constantly looking for ways to enhance students` learning experiences so they can achieve optimal result. In the increasingly advanced digital era, the use psychological tools has become an attractive approach in maximizing effective learning. This article examines the role of psychological tools in enhancing students` learning experiences and how they can be used to achieve effective learnig. This article begins by explaining the importance of positive learning experiences in influencing student motivation and engagement. Next, we identify several psychological tools than can be used to enrich learning experiences, such as social modeling, appropriate goal setting, positive reinforcement, and the use of variety in learning. In addition, this article highlights the use of technology and digital tools to maximize effective learning examples include the use of interactive media, simulations, and educational games based on psychological principles such as problem-based learning, cooperative learning, and discovery-based learning. Next, we explain how psychological tools can be used to enhance student understanding through effective metacognition settings, such as the use of strategies of self-monitoring, reflection, and problem solving, we also highlight the importance of independent learning in maximizing student learning experiences and how psychology tools can support this. This article serves as a resource for educators, curriculum developers, and education practitioners interested in using psychological tools to enhance students` learning experiences. By understanding and applying relevant psychological principles, educators can create learning environments that motivate, challenge and maximize effective learning.